2018
DOI: 10.1302/1863-2548.12.170050
|View full text |Cite
|
Sign up to set email alerts
|

Guided growth: Preliminary results of a multinational study of 967 physes in 537 patients

Abstract: BackgroundGuided growth by tension band plating is commonly used to correct coronal plane deformity. The purpose of this study was to measure the effect and further define parameters that influence results in coronal plane deformity around the knee.MethodsThe retrospective multicentre study included data on 967 physes in 537 patients, with an average follow-up of 16 months after plate insertion. Alignment analysis was compared preoperatively and in at least two measurements postoperatively, as well as with par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 24 publications
6
62
0
7
Order By: Relevance
“…Substantial deformity might also exist in the sagittal and torsional planes. Deformity in three planes increases the difficulty of any surgical intervention, but often the coronal deformity dominates and correction of this plane improves the overall picture 160,165,166 .…”
Section: Casts Insoles and Physiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial deformity might also exist in the sagittal and torsional planes. Deformity in three planes increases the difficulty of any surgical intervention, but often the coronal deformity dominates and correction of this plane improves the overall picture 160,165,166 .…”
Section: Casts Insoles and Physiotherapymentioning
confidence: 99%
“…Guided growth techniques have been gaining popularity 165 . This surgical strategy should commence early after 12 months if deformity persists despite maximized medical therapy.…”
Section: Casts Insoles and Physiotherapymentioning
confidence: 99%
“…Guided growth with hemiepiphysiodesis is a minimally invasive treatment option for mild deformities of the lower limbs. Several studies showed favourable results in children with healthy and pathological physis [34][35][36]. Depending on the deformity, the growth plate is temporarily blocked using a small plate with two screws on the medial or lateral distal femur or proximal tibia.…”
Section: Surgical Treatment Optionsmentioning
confidence: 99%
“…Существующий метод управляемого роста (гемиэпифизиодез) дает возможность эффективно выполнять коррекцию деформаций длинных костей у растущих детей при различных патологиях [11][12][13][14][15][16]. Учитывая тенденцию к рецидиву деформации у больных с кВЛСКГ, мы предположили, что последовательное применение управляемого роста (гемиэпифизиодеза) после удлинения и коррекции деформации позволит повысить качество лечения данной группы пациентов.…”
Section: актуальностьunclassified
“…Также хотелось бы остановиться на особенностях методики управляемого роста (гемиэпифизиодеза). Несмотря на крайне высокую популярность данного метода при лечении деформаций нижних конечностей у растущего ребенка на фоне разных заболеваний [11][12][13][14][15], мы не нашли какого-либо системного обзора применения данного метода у больных с деформациями на фоне консолидированного врожденного ложного сустава голени. В одной из публикаций p. Stevens [12], автора метода управляемого роста, в описании метода приведены рентгенограммы ребенка с консолидированным ложным суставом и применением гемиэпифизиодеза для коррекции вторичных деформаций.…”
unclassified